Experimental and numerical analyses of a model Trombe wall employing the natural zeolite/perlite composite plate as a thermal mass for nearly zero energy buildings - Kandilli, Canan; Gur, Muhammed; Yilmaz, Hakan; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
This study presents an in-depth experimental and numerical analysis of an innovative Composite Trombe Wall (CTW) system utilizing a natural zeolite-perlite composite plate as thermal mass, aimed at advancing sustainable building applications. This novel system uniquely combines the high specific heat capacity of natural zeolite with the low thermal conductivity of perlite, optimizing thermal storage and retention in passive solar energy applications. A comprehensive Computational Fluid Dynamics (CFD) model was developed to simulate natural convection and heat transfer dynamics, and validated against experimental data. Results indicate a maximum temperature differential of 11.5 degrees C between indoor and ambient conditions, demonstrating the CTW system's potential to enhance energy efficiency and indoor thermal comfort in nearly zero-energy buildings (nZEB). This research contributes a significant advancement by showcasing the practicality of sustainable, locally sourced materials in enhancing passive solar heating systems, thereby establishing a new benchmark in eco-friendly building technology.
Keywords: Experimental and numerical analysis; Model Trombe wall; Natural zeolite -perlite composite plates